Processing of solid state sintered α-SiC ceramics with carbon-black addition. (21st August 2019) - Çelik, Ali; Kara, Alpagut; Turan, Servet; Kara, Ferhat
Abstract: The efficient removal of surface silica layer from SiC particles by the addition of carbon is required for solid state sintering (SSS) of SiC ceramics. While wax-based organics are generally utilized as carbon source in many commercial SSS-SiC ceramics, carbon black powders with high specific surface area (SSA) are potential alternatives as carbon source, which can be dispersed in ceramic slurries directly without needing any additional pyrolysis reactions. In this study, carbon black powders were utilized as carbon source for sintering of SiC. The effect of particle size of carbon black powders on densification and microstructural development during pressureless and spark plasma sintering (SPS) were investigated. It was observed that while the density of the SiC samples increased with increasing SSA of carbon black powders, complete densification was not achieved for all samples in case of pressureless sintering due to the flaws originated by carbon black segregation on granule surfaces. SPS was found an effective sintering method for the elimination of such flaws and SiC ceramics were sintered to 100% of theoretical density independent from the particle size of the carbon black powders in this sintering technique.